Perkembangan Tafsir Perjanjian Lama dan Pembacaan Kitab Ayub Bersama Dengan Orang-orang Yang Hidup dengan HIV/AIDS - Aris Margianto (Indonesian Journal of Theology, 2017)
Throughout the long historical development of biblical hermeneutics—in phases from the implicit-practical to the theoretical reflective—consideration for the meaning of a text is determined by what is 'behind', 'inside', or 'in front of' it. Among the hermeneutical perspectives available in today's postmodern era, biblical interpretive methods can be categorized according to whether they refer to (1) the author and his world, (2) the text and its world, (3) the reader and his/her/their world, or (4) the thing and its world. Over the past few decades, approaches oriented toward the reader have gained in influence. Of profound interest is the book of Job and its reading by those who live with HIV/AIDS. The book of Job, in its presentation of the suffering person as the central figure, raises a paradox that brings readers to laughter. The book of Job is, therefore, a consoling read.